Trends in Hysterectomy Rates Associated With the Coronavirus Disease 2019 (COVID-19) Pandemic. Issue 3 (18th March 2023) - Emont, Jordan; Wen, Timothy; Friedman, Alexander M.; Wright, Jason D.
Abstract : Hysterectomy rates decreased significantly between 2019 and 2020, with the greatest declines noted from March to May of 2020, coinciding with community spread of coronavirus disease 2019 (COVID-19). Abstract : OBJECTIVE: To compare nationwide trends in the rate of inpatient and outpatient hysterectomy between 2019 and 2020 during the coronavirus disease 2019 (COVID-19) pandemic. METHODS: Using weighted data from the National Inpatient Sample and the National Ambulatory Surgery Sample, we examined the number of hysterectomies performed by month from 2019 through 2020. Monthly trends were compared between years overall, stratified by the route of surgery (abdominal, laparoscopic, and vaginal) and by indication for surgery (benign, preinvasive, cancer). Trends analyses were conducted using Joinpoint regression and reported as average monthly percentage change (AMPC). Differences in demographic characteristics between the years were compared using χ 2 tests. RESULTS: From January 2019 through December 2020, after weighting, 1, 029, 792 hysterectomies were performed, including 548, 802 (53.2%) in 2019 and 480, 990 (46.7%) in 2020. Starting in January 2020, monthly cases declined significantly, from 40, 240 to a nadir of 10, 566 hysterectomies in April 2020 (AMPC −29.2%, 95% CI −39.8% to −16.8%) ( P <.001). The subsequent months saw a significant increase in cases, from the nadir in April 2020 to 40, 023 cases in July 2020 (AMPC 39.4%, 95% CI 18.6–63.9%) ( P =.001), which then stabilized to the end of the year (AMPC −1.3%, 95% CI −4.8% to 2.4%) ( P =.46). In March 2020 there was a 24.0% decrease, in April 2020 a 74.2% decrease, and in May 2020 a 35.1% decrease compared with the respective months in 2019. The rates of vaginal hysterectomy declined more than the rates of other routes of surgery, and procedures performed for benign and preinvasive disease decreased more than those for cancer. CONCLUSION: The rate of hysterectomy in the United States decreased in 2020 compared with 2019, with the greatest decrease from March to May of 2020, corresponding with the initial wave of COVID-19.